AP-1 (bZIP) Transcription Factors as Potential Regulators of Metallothionein Gene Expression in Tetrahymena thermophila - de Francisco, Patricia; Amaro, Francisco; Martín-González, Ana; Gutiérrez, Juan Carlos (Frontiers in Genetics, 2018)
Metallothioneins (MT) are multi-stress proteins mainly involved in metal detoxification. MT gene expression is normally induced by a broad variety of stimulus and its gene expression regulation mainly occurs at a transcriptional level. Conserved motifs in the T. thermophila MT promoters have been described. These motifs show a consensus sequence very similar to AP-1 sites, and bZIP type transcription factors might participate in the MT gene expression regulation. In this research work, we characterize four AP-1 transcription factors in each of four different analysed Tetrahymena species, detecting a high conservation among them. Each AP-1 molecule has its counterpart in the other three Tetrahymena species. A comparative qRT-PCR analysis of these AP-1 genes have been carried out in different T. thermophila strains (including metal-adapted, knockout and/or knockdown strains among others), and under different metal-stress conditions (1 or 24h Cd2+, Cu2+ or Pb2+ treatments). The possible interaction of these transcription factors with the conserved AP-1 motifs present in MT promoters has been corroborated by protein-DNA interaction experiments. Certain connection between the expression patterns of the bZIP and MT genes seems to exist. For the first time, and based on our findings,a possible gene expression regulation model including both AP-1 transcription factors and MT genes from the ciliate T. thermophila has been elaborated.